Hypovitamanosis D and non cardiac chest pain - Nagabhushana, B. V.; Mahesh, G.; Subramanyam, P. S. S.; Rekha, A. (International Journal of Research in Medical Sciences, 2020)
Background: Recurrent atypical chest pain not due to cardiac illness is a very common condition in medical outpatient departments. Authors found that people consulting for atypical chest pain often have significant Vitamin D deficiency and correction of Vitamin D deficiency relieved patient symptoms. Hence authors carried out this study. Methods: Persons aged below 50 years were taken up for study. Those attending medical clinics with complaints of chest pain occurring more than two times were taken up for study. Cardiac illness was excluded by clinical examination and investigations. Those found to have low Vitamin D were taken up for study. 60,000 international units Vitamin D was administered orally weekly for 8 weeks. They were followed up twice weekly for three months and once monthly for three months. Results: Results were analyzed and charted. 120 subjects were taken up for study and duration of study was three years. Average age of the study group was 37.50 years and the average Vitamin D level was 15.75 nanogram/ml (ngm/ml). Duration of chest pain ranged from one week to one year. Most of the patients had migratory chest pain. Conclusions: As Vitamin D deficiency is a treatable medical condition it may be prudent to check Vitamin D levels in the patients presenting with recurrent atypical pain in the chest. It reduces the burden on the health care system and relieves the suffering of the patient. It may not be futile to check Vitamin D levels even in the patients with coronary artery disease who are suffering from atypical chest pain.